Microfibre abundance in aggregates exposed to varying concentrations of microfibres - Cordelia Roberts; Clara Flintrop; Alexander Khachikyan; Jana Milucka; Colin B Munn; Morten Hvitfeldt Iversen (PANGAEA, 2024)
Aggregate size or ECD is measured in mm. The video recordings were used to determine size-specific sinking velocities of the individually formed aggregates based on the method developed by Ploug et al. (2010, doi:10.4319/lom.2010.8.386). Aggregate size was measured using the projected area of aggregate and calculating equivalent circular diameter (ECD) on ImageJ. Aggregate size is measured in mm.
In: Roberts, C et al. (2024): Microfibers analysis on diatom aggregates of skeletonema marinoi in laboratory conditions [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.971557